2017
DOI: 10.1097/md.0000000000007699
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of the relationship between Modic changes and sagittal balance parameters in the cervical spine

Abstract: The aim of this study is to investigate the relationship between the Modic changes (MCs) and sagittal parameters of the cervical spine.We conducted a retrospective review of 100 outpatients with magnetic resonance imaging (MRI) scans of the cervical spine (50 male and 50 female). MRI parameters were measured, including neck tilt, T1 slope (T1 ), thoracic inlet angle (TIA), and cervical lordosis (CL: Cobb C2–7). Patients were divided into 4 groups according to the presence or absence of MC and T1s, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…As T1S decreases, a higher stress concentration is added onto the lower cervical spinal segments, such as C5–6 and C6–7, which worsens the symptoms of CS in the end and accelerates the process of degeneration. However, Ma et al [ 12 ] conducted a study that compared T1S between patients with and without Modic changes (MCs). The results showed that patients with MCs had a significantly higher T1S than those without MCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As T1S decreases, a higher stress concentration is added onto the lower cervical spinal segments, such as C5–6 and C6–7, which worsens the symptoms of CS in the end and accelerates the process of degeneration. However, Ma et al [ 12 ] conducted a study that compared T1S between patients with and without Modic changes (MCs). The results showed that patients with MCs had a significantly higher T1S than those without MCs.…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that people should have a large C2–7COBB to perform a horizontal gaze while they had a high T1S. The imbalance between C2–7COBB and T1S might be a key factor that accelerated the progression of degeneration [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted a retrospective review of 100 subjects, discussing the relationship between the cervical sagittal parameters, and the results concluded that T1 slope is a potential risk factor for the development of MC due to impaired sagittal balance, especially in the C5–C6 cervical segment [ 22 ]. Due to the limited sample size of the enrolled subjects of the previous study, we performed the present study with a total number of 300 subjects to explore the correlation between the occurrence of MC and sagittal alignment in the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for why more MCs are found on C6/7 than C4/5 in our study is interesting. Several authors have reported the effects of MCs on cervical sagittal balance and many of them suggested that patients with MCs have larger cervical curvature, larger T1 slope or C7S [21][22][23]. Higher T1 slope or C7S needs more CL to keep horizontal balance, which may cause more stress and hypermobility at the bottom of the cervical spine (C5/6 and C6/7), resulting in unusual mechanical stress and more endplate degeneration [21].…”
Section: Prevalence and Distribution Of The Cervical Mcsmentioning
confidence: 99%